New effectual configuration of bistable nonlinear energy sink - Rafath Abdul Nasar; Mohammad A. AL-Shudeifat (Scientific Reports)
Abstract The study presents a new configuration of nonlinear energy sinks (NESs) which is adaptable to function as either stable or bistable NES. The proposed NES is based on the spring-loaded inverted pendulum (SLIP) in which a torsional stiffness element couples the SLIP to the linear oscillator (LO). The bistable configuration provides a critically stable position when the SLIP is vertically aligned with respect to the LO motion. At this critical stability position, the SLIP NES incorporates pre-stored potential energy which generates the bistability characteristics resembling that of a stiffness-based bistable NES. The equations of motion of the coupled LO with the SLIP NES are derived based on the Euler–Lagrange method in non-dimensional form. The parameters of the considered SLIP NESs are optimized to achieve an optimum energy absorption from the LO. The proposed B-SLIP NES is also applied to suppress seismic ground motion and forced torsional vibrations. The obtained numerical simulation and analytical response results verify the robustness of the B-SLIP NES in vibration suppression performance compared with the tuned mass damper and the cubic stiffness NES.